The father god and traditional Christian interpretations of suffering, guilt, anger and forgiveness as impediments to recovery from father-daughter incest. - Redmond, Sheila Ann. (University of Ottawa (Canada), 1993)
The hypothesis of this dissertation suggested that certain teachings of traditional Christianity would make it difficult for a Christian daughter who was sexually assaulted by her father to successfully recover from the trauma. To see if this could be the case, I first looked at the psychological damage done to the daughter who is sexually assaulted by her father from the perspective of the research of authors such as Florence Rush, Judith Herman, E. Sue Blume, Diana Russell, Ellen Bass, Laura Davis, David Finkelhor, Louise Armstrong, Susanne Sgroi and Roland Summit. I then analyzed what little references there are to father-daughter sexual assault and physical and sexual child abuse in the literature that dealt with aspects of Christianity that were relevant to father-daughter sexual assault, in terms of occurrence of father-daughter incest in Christian environments, the impact of Christianity on the abuse and recovery, or the impact of sexual assault on Christian beliefs. Following that, I analyzed the biblical texts for their input into the problem by focusing on the story of Lot and his daughters and the kinship rules of Leviticus 18. In the same chapter, I discussed the story of eleven-year-old Maria Goretti who was canonized for resisting the sexual advances of a young man living in her household, and dying because of that resistance. There was almost nothing in either of these chapters that would suggest that there was anything in Christianity that would cause a special problem for a believing daughter who was sexually assaulted by the father save in the work of Dutch authors, Annie Imbens-Fransen and Ineke Jonkers, and the recent work of James Poling. These authors, who have worked extensively with Christian abusers and victims, indicted the patriarchal power and belief structure of traditional Christianity as a source of extreme pain for sexually assaulted Christians and for Christian abusers. After a critique of the analysis of god as a transitional god, it is suggested that in order to understand the impact of the Christian belief system on victims of father-daughter incest, it would be better to view the anthropomorphic Christian god as a second male parent for the daughter, albeit a super-father. This done, the last chapter looks at what the process of recovery should entail according to the authors mentioned in the second chapter. Aspects of the recovery process are compared to traditional Christian teachings on issues such as suffering, guilt, anger and forgiveness. It was discovered that the Christian teachings are often at odds with the necessities of the recovery process. This would mean that a Christian daughter who was sexually assaulted by her father would have to overcome resistances caused by her belief system as well as the inherent difficulties which victims have in order to become survivors.
Keywords: Religion, General.